Peran Brand Attractiveness Sebagai Variabel Intervening pada Brand Distinctiveness, Brand Prestige, Brand Sosial Benefit, dan Memorable Brand Experience Terhadap Customer Brand Identification - Kris Jati Kesuma JP; Hetty Karunia Tunjung Sari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The rapid development in the tourism sector is accompanied by an increase in foreign tourist arrivals, making the Indonesia’s hotel industry which is part of the tourism sector, growing dramatically. Competition between brands is unavoidable, each hotel must develop its own brand strategy. This study aims to add insight into brand management specifically in the hotel industry. This study used a quantitative method by distributing questionnaires to 219 respondents who lived in Jabodetabek and had stayed at five-star hotels located in Java and Bali. From this study it can be concluded that the role of brand attractiveness in giving indirect effects to brand prestige, brand distinctiveness, brand social benefits, and memorable brand experience on customer brand identification. This study also stated the importance of brand prestige, brand distinctiveness, and brand social benefits significantly and positively influences customer brand identification directly.